(3OjhGf HGeNQeIs - (3YeQ Hf YHO Gddg HGeNQeI GdgLQGfj GdTjHGfj GdMVQej,J (B952 (3g` s ((3YHO Gddg Hf YhV GdbYjWi s)
(3ChdgG (B:s
(3jGXfjfi Vfi MGdi hdG CWeY HMjdg Mjdg GdYHO ajeG bOQ Gddg bdjdg s
(3BNQgG (B:s
(3hGLYd UdGJc hGdSdGe JMagG CHkO Ydi NjQ GdCfGe hBdg SQ GdhLhO eMeO hCejQg hefjQg HebGdg haYGdg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B70s
(3HgG fXGe GdJYbjHIs
(3fSNI CNQi bUGFO efg ZjQ eQJHI hgj ef GdTYQ GdMejfi hHYVgG ef GdTYQ GdaUjMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B213s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCMbGa ecJHI eMSf Hf LYaQ Hhfei GdNGUI s
Keywords: (3GdCOHs